2019
DOI: 10.3389/fimmu.2019.02046
|View full text |Cite
|
Sign up to set email alerts
|

Plasminflammation—An Emerging Pathway to Bradykinin Production

Abstract: Plasminogen activation is essential for fibrinolysis—the breakdown of fibrin polymers in blood clots. Besides this important function, plasminogen activation participates in a wide variety of inflammatory conditions. One of these conditions is hereditary angioedema (HAE), a rare disease with characteristic attacks of aggressive tissue swelling due to unregulated production and activity of the inflammatory mediator bradykinin. Plasmin was already implicated in this disease decades ago, but a series of recent di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 71 publications
1
46
0
1
Order By: Relevance
“…The formation of immunoreactive BK (that includes Lys-BK) induced by contact system activation or by recombinant tissue kallikrein (KLK-1) did not differ between the 2 groups. This line of evidence combines with others to support the hypothesis that plasmin has an active role in the pathogenesis of HAE-C1-INH attacks ( 22 ). In the present work, we quantified the half-life (t 1/2 ) of BK in plasma samples as influenced by an ACE inhibitor added in vitro or administered in vivo to show the transient nature of BK accumulation; this has also relevance to the physiopathology of ACE inhibitor-induced AE.…”
Section: Introductionsupporting
confidence: 80%
“…The formation of immunoreactive BK (that includes Lys-BK) induced by contact system activation or by recombinant tissue kallikrein (KLK-1) did not differ between the 2 groups. This line of evidence combines with others to support the hypothesis that plasmin has an active role in the pathogenesis of HAE-C1-INH attacks ( 22 ). In the present work, we quantified the half-life (t 1/2 ) of BK in plasma samples as influenced by an ACE inhibitor added in vitro or administered in vivo to show the transient nature of BK accumulation; this has also relevance to the physiopathology of ACE inhibitor-induced AE.…”
Section: Introductionsupporting
confidence: 80%
“…FP was recipient of a PhD fellowship from EFS APR2016. Faidra Parsopoulou 1,2,3 Delphine Charignon 4 Maud Tengo 4 Fotis Psarros 5…”
Section: Fu N D I N G I N Fo R M Ati O Nmentioning
confidence: 99%
“…Coen Maas 6 Teresa Gonzalez-Quevedo 7 Christian Drouet 3,8 Anastasios E. Germenis 1,2 Accumulating evidence suggests that both IL-1β and IL-17A are crucially involved in IVIG resistance in KD patients. [1][2][3][4][5][6] We previously demonstrated that IVIG could specifically and completely suppress TNF-α-induced, but not IL-1β-induced, protein production of such KD-related cytokines as IL-6 and G-CSF by HCAECs. 7 Furthermore, the dramatic and specific anti-inflammatory effects of IVIG were associated with complete inhibition of C/EBP activity.…”
Section: Fu N D I N G I N Fo R M Ati O Nmentioning
confidence: 99%
“…[18][19][20] This shows that plasmin-dependent bradykinin production is regulated by ACE activity. 21 It is possible that a similar mechanism, linking the fibrinolytic system and the plasma contact system, drives bradykinin production in COVID-19 and enhances pathology. 21 Although most bradykinin is directly degraded (►Fig.…”
Section: Kinin Degradationmentioning
confidence: 99%
“…21 It is possible that a similar mechanism, linking the fibrinolytic system and the plasma contact system, drives bradykinin production in COVID-19 and enhances pathology. 21 Although most bradykinin is directly degraded (►Fig. 1), around 11% of bradykinin is converted (62 AE 10 nmolÁminute À1 ÁmL À1 ) into des-Arg 9 -bradykinin by carboxypeptidase M or N. In comparison with bradykinin, the half-life of des-Arg 9 -bradykinin is at least 10-fold higher (643 AE 436 seconds).…”
Section: Kinin Degradationmentioning
confidence: 99%